2015
DOI: 10.1007/s13277-015-4359-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic factors in localized high-grade undifferentiated pleomorphic sarcoma: report of a multi-institutional experience of Anatolian Society of Medical Oncology

Abstract: Most data on prognostic factors for patients with high-grade undifferentiated pleomorphic sarcoma (HGUPS) is obtained from analyses of soft tissue sarcomas. The purpose of this study was to evaluate the clinicopathologic features and their impact on outcomes specifically in patients diagnosed with HGUPS. In this multicenter trial, we retrospectively analyzed 112 patients who were diagnosed and treated at 12 different institutions in Turkey. We collected data concerning the patients, tumor characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
5
4
1
3
Order By: Relevance
“…There was no significant effect of the deep tumor associated with LRFS in some literature, and our study was in line with them. However, we observed that deep tumor had a worse outcome on MFS, which was consistent with Ozcelik’s study 24…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was no significant effect of the deep tumor associated with LRFS in some literature, and our study was in line with them. However, we observed that deep tumor had a worse outcome on MFS, which was consistent with Ozcelik’s study 24…”
Section: Discussionsupporting
confidence: 93%
“…As for resection quality, our study revealed that R0 resection was a favorable prognostic factor for overall survival and local recurrence survival, while there was no significant difference for MFS between patients with R0 resections and patients with R1/R2 resections. Our results were supported by previous studies,14,16,23,24,26 and these data manifested that clear surgical margin was a favorable prognostic factor for local recurrence. So we tried our best to obtain a clear surgical margin and advocated extended resection for patients who had unplanned resections in our center.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies vary regarding the efficacy of brachytherapy for local control of extremity soft tissue sarcomas, with extensive variability in tumor grade, size, depth, histologic diagnoses, margin status, and brachytherapy technique. As such, a broad range of local recurrence data exist, ranging between 18% to 78% [22,26,28,42,43,50] for HDR-BT alone, and between 0% and 85% when brachytherapy is combined with EBRT [5,9,12,19,34,36,39,45]. Large series have shown that unplanned excision is associated with an increased risk for local recurrence [47,48].…”
Section: Discussionmentioning
confidence: 99%